(untitled) (Scientific journal of the Fergana State University, 2025)
In this article the effect of concentration and temperature on the viscosity of purified sodium-carboxymethylcellulose (CMC) and polymermetallokomplexes solutions is studied. The relationship between the complete dissolution times and viscosities of the purified 1, 2 and 3% CMC solutions with a selected degree of substitution 0.88 and a degree of polymerization 900 was determined. An aqueous solution of 1, 2 and 3% CMC was prepared and its rheological parameters were determined. It was found that the viscosity of the solutions increased when CMC solutions were exposed to the same amount of silver nitrate (AgNO3) salt. The polymermetallokomplexes compound synthesized on the basis of CMC and AgNO3 solutions was proved by rheological and FTIR spectroscopy studies.